Magneto-rheological Defects and Failures: A Review - S. A., Wahid; I., Ismail; M. S. A., Rahim (IOP Publishing, 2016)
Magneto-rheological fluid is the colloidal suspension of micron sized magnetic particles in a carrier fluid where defects and failures occur at many circumstances. This paper presents a review on defects and failures of magneto-rheological fluid in engineering applications. The most significant defect is hard cake which developed due to re-dispersion difficulties of remnant particles magnetization, leaving the magneto-rheological fluid ineffective. Clumping effect on the other hand is a separation of carrier fluid from the magnetic particles when magneto-rheological fluid is being exposed to higher magnetic field for an extended period of time. As clumping occurred, it leads to Fluid Particle Separation (FPS) which is believed altering the strength distribution of magneto-rheological fluid and therefore reducing the squeezing force. Another significant failure is magnetic particles oxidation of the magneto-rheological fluid. This paper also will discuss on stability problems which is the most challenged issue in magneto-rheological fluid technology. With the comprehensive review in this paper, researcher can design materials of magneto-rheological fluid for better properties.